Impact of Provenance on Phytochemical Attributes of pigmented Landrace Maize Varieties - Majamanda, James; Katundu, Mangani; Ndolo, Victoria; Tembo, David (Journal of Science and Technology, 2022)
Maize is one of the most diverse cereal crops that contribute highly in calorie supply to human diet. Pigmented maize secondary metabolites which are phytochemicals of healthy importance include carotenoids and phenolics which act as precursors of vitamin A and antioxidants respectively. Pigmented landrace maize is cultivated by smallholder farmers in their localities. Three different pigmented maize varieties from different growing districts were analysed for total carotenoids content (TCC) and total phenolic content (TPC), using spectrophotometer. The districts experience a warm temperate climate and higher rainfall in summer than in winter but they differ in that Ntcheu has highest average annual temperature of 20.3°C while Dedza receives the highest annual precipitation of about 1010 mm. Mzimba has an average annual temperature of 20.1°C and receives about 915 mm of precipitation annually. Individual carotenoids were analysed using high performance liquid chromatography (HPLC). TCC were significantly higher (p < 0.05) in Ntcheu and Mzimba provenances compared to Dedza. Lutein (22.84 ± 1.25 µg/g) and Zeaxanthin (23.16 ± 2.44 µg/g) were highest in landrace orange maize from Ntcheu. Mzimba provenance showed highest beta-cryptoxanthin (8.60 ± 2.15 µg/g). TPC were not significantly different between Dedza (204.29 ± 0.35 mg/Kg) and Mzimba (207.65 ± 0.22 mg /kg) red maize. Ntcheu provenance showed the least TPC (184.06 ± 0.61 mg/Kg). It seems provenance influenced phytochemical attributes of pigmented landrace maize varieties in some instances. This study also revealed that post-harvest handling of pigmented landrace maize affects phytochemical content. Care should, therefore, be taken in handling pigmented landrace maize to avoid phytochemical loses. Farmers and all other stakeholders in Malawi are encouraged to produce and include pigmented landrace maize varieties in their diets in order to gain the associated health benefits. Further studies are needed for complete characterisation of phenolic compounds of pigmented landrace maize of Malawi.